Evaluation of the effect of enoxolone-containing toothpaste on dental plaque, gingival inflammation and bleeding indices - Sara Valizadeh; Ladan Ranjbar Omrani; Zohreh Moradi (Tehran University of Medical Sciences, 2020)
Background and Aims: Enoxolon is a natural licorice and its formula is similar to cortisone. The aim of this double blind randomized match control clinical trial, was to analyze the effect of Arthrodont toothpaste containing 1% Enoxolone on dental plaque, gingival inflammation, and bleeding indices. Materials and Methods: 40 patients who had gingivitis were selected. They were instructed to brush their teeth twice daily for three minutes then massage the gums with pastes for one minute and then wash their mouths. The patients were divided into two groups: The Arthrodont toothpaste containing Enoxolon, was given to the study group and the Crest toothpaste free of Enoxolon, was given to the control group. At the beginning of the study and after 21 days, plaque, gingival, and bleeding indices were measured. The statistical analyses were done by Paird T test, T test and nonparametrical analysis of Wilcoxon and Mann-Whitney. Results: In both groups, the three indices decreased significantly. Comparing between the two groups, the gingival and bleeding indices had significantly decreased in the study group (Arthrodont toothpaste) compared to the control group (Crest toothpaste). However, no significance difference in the plaque index between the two groups was found (P=0.143). Conclusion: The results of this clinical study showed that Enoxolon had anti-inflammatory effect on gingivitis.